Comparative results of percutaneous and open surgery for trigger fingers: a propensity score analysis - Chanthanapodi, Praphan; Aodsup, Sasithorn (Frontiers in Surgery, 2025)
Background and objectivesTrigger finger is a common hand condition characterized by the locking of a digit, often requiring surgical intervention when conservative treatments fail. This study aimed to compare the outcomes of a modified percutaneous release technique with those of traditional open release surgery.Materials and methodsA retrospective cohort study was conducted on 245 patients (287 digits), of which 161 digits underwent open release and 126 underwent percutaneous release. A modified technique for percutaneous release was described. Propensity score matching was used to balance the data. Cox regression and Laplace regression were applied to analyze the hazard ratio and median survival time for pain relief and time to return to work. Adverse events were also reported.ResultsThe duration of pain relief in the percutaneous release group was shorter than that in the open release group (hazard ratio = 1.73, 95% CI: 0.98–3.06; p = 0.057). Fifty percent of patients in the percutaneous release group experienced pain relief within two days, compared to seven days in the open release group (p = 0.003). Time to return to work was significantly shorter in the percutaneous release group than in the open release group (hazard ratio = 2.93, 95% CI: 2.08–4.13; p < 0.001). Fifty percent of patients in the percutaneous release group returned to work within three days, compared to 15 days in the open release group (p < 0.001). Three digits (2.4%) required conversion to open release due to the failure of percutaneous release. No nerve injuries or recurrences were observed at a follow-up of 42.2 ± 2.2 months.ConclusionsPercutaneous release resulted in an earlier return to work and a high success rate (97.6%) with no nerve injuries or recurrences over 42 months. Despite a 2.4% failure rate, careful technique minimized complications. Further randomized trials are needed to confirm these findings and optimize patient selection.